Omaha Beach on D-Day - Morvan, Jean David 1969-; Tréfouël, Séverine 1981-; Lebrun, Bernard (First Second, 2015)
Graphic story based on Robert Capa's attendance at and photographs of the Operation Neptune landing operation on June 6, 1944, (D-Day) of the Allied invasion of Normandy, with essays that detail the events of the D-Day landing